2022
DOI: 10.3390/cancers14174314
|View full text |Cite
|
Sign up to set email alerts
|

IRF4 as an Oncogenic Master Transcription Factor

Abstract: IRF4 is a transcription factor in the interferon regulatory factor (IRF) family. Since the discovery of this gene, various research fields including immunology and oncology have highlighted the unique characteristics and the importance of IRF4 in several biological processes that distinguish it from other IRF family members. In normal lymphocyte development and immunity, IRF4 mediates critical immune responses via interactions with upstream signaling pathways, such as the T-cell receptor and B-cell receptor pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…In addition, we also observed that 14g or 14h significantly down-regulated other proteins (Figure 8A,B and Figure S3), such as TP53RK, 69 STAT1, 70 STAT2, 71 IRF4, 72,73 CDK5, 74 and KRAS. 75,76 Studies have shown that these proteins are closely related to the occurrence and development of hematological malignancies.…”
mentioning
confidence: 57%
“…In addition, we also observed that 14g or 14h significantly down-regulated other proteins (Figure 8A,B and Figure S3), such as TP53RK, 69 STAT1, 70 STAT2, 71 IRF4, 72,73 CDK5, 74 and KRAS. 75,76 Studies have shown that these proteins are closely related to the occurrence and development of hematological malignancies.…”
mentioning
confidence: 57%
“…Unlike other IRFs, IRF4 is a unique family member that is not regulated by interferons (IFNs) ( 22 ), instead, is mainly induced upon T-cell receptor (TCR) signaling, Toll-like receptors (TLRs; such as TLR4 and TLR9) and tumor necrosis factor receptors. The expression of IRF4 is restricted to immune cells, including T and B cells, macrophages and DCs ( 19 , 22 ). In naïve T cells, IRF4 is expressed at low levels ( 23 ); however, following TCR signaling it is immediately induced and mediates critical immune responses by interacting with upstream signaling pathways, such as the TCR signaling, and its diverse binding partners ( 26 ).…”
Section: Structure and Function Of Irf4mentioning
confidence: 99%
“…Interferon regulatory factor 4 (IRF4) is a member of the interferon regulatory factor (IRF) family, and its unique characteristics and the importance in multiple biological processes have been highlighted by oncology and immunology. It first serves as an oncogene or a tumor suppressor in multiple types of lymphoid neoplasms ( 19 21 ). In addition, intriguingly, accumulating studies have demonstrated that IRF4 is a central determinant of differentiation, activation and effector function for various immune cells ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…
the oncogenic transcriptional program in malignant lymphoid cells 15 . However, research on the role of IRF4 in OSCC is still lacking 16 .In this study, we conducted a comprehensive bioinformatics analysis including functional enrichment analysis, CNV and immune infiltration analysis through Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases to identify key genes and explore the underlying molecular mechanisms involved in OSF into OSCC.
…”
mentioning
confidence: 99%
“…the oncogenic transcriptional program in malignant lymphoid cells 15 . However, research on the role of IRF4 in OSCC is still lacking 16 .…”
mentioning
confidence: 99%